Features of Hydrogen-Enriched Methane–Air Flames Propagating in Hele-Shaw Channels - Sergey Yakush; Sergey Rashkovskiy; Maxim Alexeev; Oleg Semenov (Energies)
Mixtures of hydrogen with common hydrocarbon fuels are considered viable for reducing carbon footprint in modern industry, power production, and transportation. The addition of hydrogen alters the kinetics and thermophysical properties of the mixtures, as well as the composition and properties of combustion products, requiring detailed research into the features of flame propagation in hydrogen-enriched hydrocarbon–air mixtures. Of particular interest are also the safety aspects of such fuels. In this paper, experimental results are presented on the premixed laminar flame propagation in channels formed by two closely spaced plates (Hele-Shaw cell), with the internal straight walls forming a diverging (diffuser) channel with the opening angles between 5 and 25 degrees. Methane–hydrogen–air mixtures with the hydrogen relative contents of 0%, 25%, and 50% and global equivalence ratio of unity were ignited by a spark near the closed narrow end of the channel. Experiments were performed with the gap width of 3.5 mm; video recordings were processed in order to determine the quantitative features of the flame front propagation (leading and trailing point coordinate, coordinates of the cusps, cell sizes and shapes). The main features of flame propagation (fast initial expansion, development of cellular flame, self-induced longitudinal oscillations) are obtained and compared to clarify the effect of hydrogen contents in the fuel and channel geometry (gap width, opening angle).